We are given that the position of an object if given by the following equations:
![\begin{gathered} x=-3t^2+2t-4 \\ y=-2t^3+6t^2+1 \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/u20adyh2gj3fsszmn23zqttlnq3zb2086d.png)
To determine the velocity we will determine the derivative of each of the functions. For "x" we have:
![x=-3t^2+2t-4](https://img.qammunity.org/2023/formulas/physics/college/y00dfbsbubh3b6isnbxfmn9meibwyya417.png)
Finding the derivative with respect to time we get:
![(dx)/(dt)=(d)/(dt)(-3t^2+2t-4)](https://img.qammunity.org/2023/formulas/physics/college/4enj9cm9d17xetk2qy3qt0rplyh31vvc3r.png)
Now we distribute the derivative on the left side:
![(dx)/(dt)=(d)/(dt)(-3t^2)+(d)/(dt)(2t)-(d)/(dt)(4)](https://img.qammunity.org/2023/formulas/physics/college/8zuvt4c5gkjaz1q3s4r61n8e4qkwxlljx9.png)
For the first derivative we will use the rule:
![(d)/(dt)(at^n)=ant^(n-1)](https://img.qammunity.org/2023/formulas/physics/college/p79s4sacry3jrr43dveg189rrxi8e551ym.png)
Applying the rule we get:
![(dx)/(dt)=-6t^{}+(d)/(dt)(2t)-(d)/(dt)(4)](https://img.qammunity.org/2023/formulas/physics/college/1556v8a5pbucxa22k6k0dtwcqwf9s0nntu.png)
For the second derivative we use the rule:
![(d)/(dt)(at)=a](https://img.qammunity.org/2023/formulas/physics/college/3cs4pewol86y31fqfu7awfo9agv2mv04nr.png)
Applying the rule we get:
![(dx)/(dt)=-6t^{}+2-(d)/(dt)(4)](https://img.qammunity.org/2023/formulas/physics/college/vs5651127uyto68gprooanenw31kmcphgx.png)
For the third derivative we use the rule:
![(d)/(dt)(a)=0](https://img.qammunity.org/2023/formulas/physics/college/59pyhx2v9acdf1sw26r1hphhkuv6l5f5lv.png)
Applying the rule we get:
![(dx)/(dt)=-6t^{}+2](https://img.qammunity.org/2023/formulas/physics/college/t288xkp0854880l0sml770z13ij9nz0779.png)
Now, since the velocity is the derivative with respect to time of the position and this is and we determine the derivative for the x-position what we have found is the velocity in the x-direction, therefore, we can write:
![v_x=-6t^{}+2](https://img.qammunity.org/2023/formulas/physics/college/ee11fbeb7tmnu81bndy0a056koaksgopr9.png)
Now we substitute the value of time, t = 1, we get:
![\begin{gathered} v_x=-6(1)+2 \\ v_x=-6+2 \\ v_x=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/qjnecom2abmtmxcesq4duth86u4ojback7.png)
Now we use derivate the function for "y":
![(dy)/(dt)=(d)/(dt)(-2t^3+6t^2+1)](https://img.qammunity.org/2023/formulas/physics/college/tofxfhprvizbi96zkbiyvllemrth6nj5gh.png)
Using the same procedure as before we determine the derivative:
![(dy)/(dt)=-6t^2+12t](https://img.qammunity.org/2023/formulas/physics/college/fqaml7yagu007mz8vz4h5ka9izugdt15gp.png)
This is the velocity in the y-direction:
![v_y=-6t^2+12t](https://img.qammunity.org/2023/formulas/physics/college/orphtn7bw5ofm5190accj8j56aev234gvz.png)
Now we substitute the value of t = 1:
![\begin{gathered} v_y=-6(1)^2+12(1) \\ v_y=6 \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/zbyt8y4u2coce10b2gbdmm16n52s9hv9ly.png)
Now, the speed is the magnitude of the velocity, the magnitude is given by:
![v=\sqrt[]{v^2_x+v^2_y}](https://img.qammunity.org/2023/formulas/physics/college/b1061y4obi6re8od41e46k9muims0av3n1.png)
Substituting the values we get:
![v=\sqrt[]{(-4)^2+6^2}](https://img.qammunity.org/2023/formulas/physics/college/24zlajewu44am3ztlvw6wk63s96tpk6xgc.png)
Solving the operations:
![v=7.21](https://img.qammunity.org/2023/formulas/physics/college/908sm3triwrhcdgb0t4fe2zsb54n64ea04.png)
Therefore, the speed is 7.21 m/s.
To determine the acceleration we will determine the derivative of the formulas for velocities:
![v_x=-6t^{}+2](https://img.qammunity.org/2023/formulas/physics/college/ee11fbeb7tmnu81bndy0a056koaksgopr9.png)
Now we derivate with respect to time:
![(dv_x)/(dt)=a_x=-6](https://img.qammunity.org/2023/formulas/physics/college/jviy3fca02lm6keo9qpyz5r2ghvwg0w6xt.png)
Now we use the function for the velocity in the y-direction:
![(dv_y)/(dt)=a_y=-12t^{}+12](https://img.qammunity.org/2023/formulas/physics/college/ijeyvuew9wn5ix2ce5ztsrcg7xdvzh4s4g.png)
Now we substitute the value of t = 1:
![\begin{gathered} a_y=-12(1)^{}+12 \\ a_y=0 \end{gathered}](https://img.qammunity.org/2023/formulas/physics/college/6v8f9v0a8cqwyj2xabo8p6ggf9d4gmvmd1.png)
Since the acceleration in the y-direction is zero, this means that the total acceleration is the acceleration in the x-direction, therefore, the magnitude of the acceleration is:
![a=6](https://img.qammunity.org/2023/formulas/mathematics/high-school/qm3jky8slegs3vcrteii35z52p67vwagyh.png)